2010
DOI: 10.1103/physrevd.81.114039
|View full text |Cite
|
Sign up to set email alerts
|

Does stability of relativistic dissipative fluid dynamics imply causality?

Abstract: We investigate the causality and stability of relativistic dissipative fluid dynamics in the absence of conserved charges. We perform a linear stability analysis in the rest frame of the fluid and find that the equations of relativistic dissipative fluid dynamics are always stable. We then perform a linear stability analysis in a Lorentz-boosted frame. Provided that the ratio of the relaxation time for the shear stress tensor, τ π , to the sound attenuation length, Γ s = 4η/3(ε + P ), fulfills a certain asympt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
191
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(209 citation statements)
references
References 58 publications
(95 reference statements)
15
191
0
3
Order By: Relevance
“…In conventional hydrodynamics, higher-order terms are required to render the theory causal [28] (see e.g. [2,29] for more recent discussions). We expect that a causal formulation of MHD will involve higher-order relaxation times as well as the electric field dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional hydrodynamics, higher-order terms are required to render the theory causal [28] (see e.g. [2,29] for more recent discussions). We expect that a causal formulation of MHD will involve higher-order relaxation times as well as the electric field dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In [28] the authors suggested that the problem of acausality and instability are correlated in relativistic dissipative hydrodynamics.…”
Section: Stability and Causalitymentioning
confidence: 99%
“…We followed closely the study performed in [28] for the Israel-Stewart theory where the dispersion relation (13) and the decomposition of its modes in real and imaginary parts were considered in the large and small wavenumber limits. In [28] the authors suggested that the problem of acausality and instability are correlated in relativistic dissipative hydrodynamics.…”
Section: Stability and Causalitymentioning
confidence: 99%
See 2 more Smart Citations